Forging Nonprofit Accounting Principles. - Seidler, Lee J.; Weinstein, Edward A. (The Accounting Review, 1978)
Five years ago, Congress established The Commission on Private Philanthropy and Public Needs to study public philanthropy in the U.S. One of the Commission's most significant findings was that accounting methods employed by nonprofit organizations were not codified, were outdated, and could result in abuses of financial disclosure. In response to these findings, the American Institute of Certified Public Accountants established a group to study the problem and ultimately to codify new rules of accounting and disclosure. This group, the Non-profit Organizations Subcommittee of the Accounting Standards Executive Committee, published a discussion draft in February 1977. The Subcommittee received and reviewed some 300 responses from individuals and organizations to the discussion draft. An exposure draft containing revisions of the original discussion draft was published in April 1978. Some may wonder why accountants had not written such rules earlier. It was because most attention had been focused on commercial enterprise accounting. Also, the nonprofit area was not recognized as large enough to warrant attention, nor was it perceived that significant abuses could occur or were occurring.